Caracterización del sistema de Tenencia y Morfológica del Asno Criollo Ecuatoriano en la Provincia de Tungurahua. - Santos Rivadeneira, Rudy Maximiliano (2018)
The Creole donkey is in danger of extinction, which is why its characterization is required in an integral way for the elaboration of a program for its conservation. The present job has as objective: Characterization of the tenure and morphological system of the Ecuadorian Criollo donkey at Tungurahua province as contribution to genetic improvement. The tenure system and its morphological structure were evaluated. A survey was applied to 100 donkey owners on Ambato, Baños, Pelileo and Píllaro cantons from Tungurahua province. 16 body measurements were made from which morphological indices were determined on 100 animals, the morphometric characteristics were determined by means of a zoomometric rod and data standardization by descriptive statistics, based on average statisticians, standard deviation, coefficient of variation, error standard according to age, genden and the sampling region. There is little information over this species, with poor research, making it difficult to manage them, conservation which puts on of this genetic animal resource. It was determined that Pearson correlation exists, with the morphometric obtained values from Donkeys of the Tungurahua province, with other donkeys. Obtaining as a result that the zoomometric classified indexes the creole donkey as longilineum and dolichocephalo. In most of the morphological variables, a sexual dimorphism prevailed towards the males. The conservation of this genetic animal resource is a basic pillar for future development livestock, compatible with the protection environment and respecting the cultural, historical and social animal richness and genetic plant resources. The characterization is key to establish the bases for the conservation projects elaboration.